The king's equal - Paterson, Katherine; Woodbridge, Curtis (New York, NY : HarperTrophy, 1999)
In order to wear the crown of the kingdom, an arrogant young prince must find an equal in his bride. Instead, he finds someone far better than he.
"A Trophy chapter book"--Cover.
Originally published in picture book format.
"RLE 3.2"--P. [4] of cover.